2008
DOI: 10.1177/0021886307313794
|View full text |Cite
|
Sign up to set email alerts
|

Implementation Activities and Organizational Sensemaking

Abstract: Corporate change initiatives trigger a series of activities aimed at implementing change. It is often assumed that successful implementation requires consistent action based on a shared understanding of the changes among employees. This article examines how implementation activities affect individual and organizational sensemaking processes and thereby contribute to a shared understanding and consistent change action. Based on inductive analyses of longitudinal data, the study suggests that many implementation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
84
0
17

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(112 citation statements)
references
References 42 publications
3
84
0
17
Order By: Relevance
“…8 Sensemaking has been applied as a means to understand and explain how managers at different organisational levels initiate, get acceptance for and implement organisational change (e.g. Gioia and Chittipeddi, 1991;Rouleau, 2005;Rouleau and Balogun, 2011;Stensaker, Falkenberg and Grønhaug, 2008). In this paper, we pay attention to how middle managers in a public client organisation develop mutual understanding of a political directive regarding energy-efficiency of buildings as well as to how they influence people in their surroundings to adopt their views.…”
Section: Sensemaking and Discursive Activitiesmentioning
confidence: 99%
“…8 Sensemaking has been applied as a means to understand and explain how managers at different organisational levels initiate, get acceptance for and implement organisational change (e.g. Gioia and Chittipeddi, 1991;Rouleau, 2005;Rouleau and Balogun, 2011;Stensaker, Falkenberg and Grønhaug, 2008). In this paper, we pay attention to how middle managers in a public client organisation develop mutual understanding of a political directive regarding energy-efficiency of buildings as well as to how they influence people in their surroundings to adopt their views.…”
Section: Sensemaking and Discursive Activitiesmentioning
confidence: 99%
“…The more social-psychologically informed literature (Spillane et al, 2002;Bartunek et al, 2006;Avey et al, 2008;Stensaker et al, 2008) suggests that activation of the social cognition processes of sense-making does not fully account for how individuals mediate an understanding of the process of change. In this light, Bartunek et al (2006) and Avey et al (2008) advance the idea that affect and emotions have a role in mediating individuals' behaviours during their negotiation of change processes.…”
Section: Towards a Policy Social Psychologymentioning
confidence: 99%
“…The existing social-psychological literature (Spillane et al, 2002;Bartunek et al, 2006;Avey et al, 2008;Stensaker, 2008), in acknowledging that the activation of the 46 I. Sheikh & C. Bagley social cognition processes of sense-making does not fully account for how individuals mediate an understanding of the process of change, advances the notion that affect and emotions may have a role in mediating individuals' behaviours during their negotiation of change processes. Moreover, the conceptual notion of core affect advanced by Russell (2003), as being systemically present and situationally fluid in terms of its activation levels in response to external conditions, raises additional questions on the possible impact of affect and emotions as mediating factors influencing the responses of individuals with change processes associated with policy enactment.…”
Section: Introductionmentioning
confidence: 99%
“…Greenberg (1995, p. 185) defined sense-making as 'the process whereby organizational members translate an organizational event and construct a meaningful explanation for that event' based on what they see around them. While it may be impossible to discern the cognitive processes that occur inside the heads of individuals, the outcomes of sense-making are more easily available in the form of the discursive accounts individuals produce of the new event (Stensaker, Falkenberg and Gronhaug 2008) or in the attitudes and reactions they develop toward the event (Fisher and Howell 2004). The sense-making perspective has been widely used in research on organizational change to explain (mainly by means of case studies) how contextual variables influence employees' interpretations of and responses to change and how such responses in turn influence change outcomes (e.g.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…A considerable body of studies has shown how certain groups -mainly organizational leaders -orchestrate cues and attempt to manage the meaning employees attach to organizational events and thus their response to such events (e.g. Gioia and Chittipeddi 1991;Maitlis 2005;Stensaker et al 2008). Sense-giving strategies include making messages appear logical and reasonable or framing messages around appeals to the values and norms of recipients (Bartunek, Krim, Necochea and Humphries 1999).…”
Section: Theory and Hypothesesmentioning
confidence: 99%